SAT0202 C4 LEVELS AS PREDICTOR OF DISEASE FLARES AND ADVERSE PREGNANCY OUTCOMES IN SYSTEMIC LUPUS ERYTHEMATOSUS PREGNANCIES. (2nd June 2020) - Crisafulli, F.; Gerardi, M. C.; Filippini, M.; Gorla, R.; Fredi, M.; Lazzaroni, M. G.; Taglietti, M.; Nalli, C.; Zatti, S.; Zanardini, C.; Lojacono, A.; Andreoli, L.; et al.
Abstract : Background: SLE pregnancies have an increased risk of Adverse Pregnancy Outcomes (APO). In clinical practice, low C3 and C4 levels are associated with active disease and, during pregnancy, complement activation products are shown to be associated with APO. Objectives: To analyse potential association between C3 and C4 variations and disease flares and APO during SLE pregnancies. Methods: Demographic, clinical and laboratory data on SLE pregnancies prospectively-followed by a multidisciplinary team in a pregnancy clinic from 1987 to 2015 were retrospectively analysed at preconception and at each trimester. Hypocomplementemia was defined according to the normality range calculated in healthy pregnancies by Reggia et al 1 . APO were defined as: early miscarriage (<10 th week), intrauterine fetal death (>10 th week), perinatal death (<30 th day of life), pre-eclampsia (PE), severe preterm birth (<34 th week). Results: 134 pregnancies in 98 SLE patients were analysed. APO occurred in 22 (16%) pregnancies: 9 early miscarriages, 4 intrauterine fetal deaths, 3 severe preterm births, 6 PE (hesitated in 1 intrauterine fetal death, 1 perinatal death; 2 preterm birth between 34 th and 37 th weeks and 2 term births). 13 flares (2 renal, 4 articular, 6 cutaneous and 1 neurological) were recorded in 11 (8%) pregnancies. The mean C3 and C4 levels at each trimester are shown in table 1 . Both in pregnancies with flares and with APO, there was no increase of C3 between the 2 nd and the 3 rd trimester and of C4 between the 1 st and the 2 nd trimester. At preconception, mean levels of C4 were lower in pregnancies with flares compared to those without flares (images 1 and 2); during the 2 nd and the 3 rd trimesters the mean levels of both C3 and C4 were lower in pregnancies with flares. In pregnancies with APO, the variation of C4 levels between the 2 nd and the 3 rd trimester was lower than in pregnancies without APO (-3.18 vs 0.27; p=0.01). A higher frequency of low C4 was observed at pre-conceptional visit, 1 st trimester and 3 rd trimester (6/7 vs 25/103 p=0.002; 8/9 vs 56/106 p=0.04; 9/11 vs 33/96 p=0.003) in pregnancies with flare as compared with pregnancies without flares. Conclusion: In our cohort of prospectively-followed SLE pregnancies, low C4 levels at preconception seems to predict flares during pregnancy. Low increase of C4 levels between the 2 nd and the 3 rd trimester could predict an APO. References: [1]Reggia R. et al. Rheumatology 2012;51:2186-90 Disclosure of Interests: None declared